1999
DOI: 10.1038/sj.bmt.1701985
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of peripheral blood stem cells with IVE and G-CSF improves CD34+ cell yields and engraftment in patients with non-Hodgkin’s lymphomas and Hodgkin’s disease

Abstract: Summary:The transplantation of mobilised peripheral blood stem cells is associated with more rapid engraftment than marrow transplantation. We have previously reported that G-IVE (G-CSF, ifosphamide, VP-16, epirubicin) improves the yield of CD34 ؉ cells mobilised in patients with lymphoproliferative disorders compared with cyclophosphamide 3 g/m 2 and G-CSF (G/CYCLO). In this study we have extended these observations to a larger series of patients including different lymphoma subtypes. Ninety-seven patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…17 Min et al 22 compared rhG-CSF starting on day 2 or 8 after infusion of CY in 30 patients, and they too found no difference between the two groups with regard to collection yield, toxicity or engraftment characteristics. Similarly, Haynes et al and McQuaker et al 18,19 reported the late administration of rhG-CSF after mobilization chemotherapy in patients with lymphomas. In both studies, patients achieved successful PBSC mobilization in terms of total CD34 þ cell yields.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…17 Min et al 22 compared rhG-CSF starting on day 2 or 8 after infusion of CY in 30 patients, and they too found no difference between the two groups with regard to collection yield, toxicity or engraftment characteristics. Similarly, Haynes et al and McQuaker et al 18,19 reported the late administration of rhG-CSF after mobilization chemotherapy in patients with lymphomas. In both studies, patients achieved successful PBSC mobilization in terms of total CD34 þ cell yields.…”
Section: Discussionmentioning
confidence: 86%
“…It has to be noted that in most of these studies, the primary objective was not to evaluate 'late' administration of rhG-CSF. [16][17][18][19][20][21] These studies have evaluated the 'late' use of rhG-CSF (4 days after chemotherapy), at varied doses and schedules with comparable results with those obtained after starting rhG-CSF immediately after chemotherapy. 18,19,21 Mollee et al 16 compared CY þ rhG-CSF with CE þ rhG-CSF of 10 mg/kg once daily for PBSC mobilization in patients with lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,[26][27][28][29] We do not yet know the minimal safe number of CD34 ϩ cells needed for clinical engraftment of all lineages, as this may vary depending on the stem and progenitor cell subset composition in a given patient or autograft. [42][43][44][45][46] However, we do know that a graft content of more than 5-10 million Table 1a Overall median number of CD34 + cells from nine studies of haematological recovery following autologous stem cell reinfusion 26,28,[47][48][49][50][51][52][53][54] In a survey of 1600 patients from nine published papers, including a minimum of 50 patients each, it is concluded that the overall median time to ANC and platelet recovery is 11 days (2-93) and 11 days (0-1000ϩ), respectively. From 15 studies with information of reinfused low numbers (Table 1a and b), it is concluded that no definite lower level exists to document groups of patients at high risk for prolonged recovery, based on CD34 numbers below 1 million/kg, 55 48 From such data, it is obvious that we will never obtain an exact number of CD34 ϩ cells delineating an insufficient or safe graft.…”
Section: First Step In Quality Assessment Was Cd34 Standardisationmentioning
confidence: 99%
“…A femoral Hickman line had been inserted for this purpose without complication. As our target number of CD34 + cells for autologous PBSC transplant is Ͼ5 × 10 6 /kg, 3 and because we wanted a higher CD34 + cell number in this patient to ensure rapid haemopoietic recovery, we repeated the PBSC mobilisation using IVE and G-CSF as previously described. 3 This resulted in the collection of 2.45 × 10 6 /kg CD34 + cells in a further three aphereses.…”
mentioning
confidence: 99%